Integrating Satisfaction and Cultural Background in the Customer Journey: A Method Development and Test. Issue 2 (15th March 2017) - Canfield, Daniel de Salles; Basso, Kenny
ABSTRACT: The purpose of this study was to develop and test a method to map the customer journey along the service process, integrating customer satisfaction and cultural background, and to improve the managerial applications of the customer journey method. This research applied a sequential mixed-method approach, with 34 clients participating in an observation technique and 6 customers participating in a semi-structured interview to define the restaurant customer journey and the influence of the Brazilian culture. Based on the results, an internet-mediated questionnaire was conducted among 131 participants to measure the customer satisfaction of the entire customer journey.